Socio-economic impacts of natural disasters : a gender analysis - Bradshaw, Sarah (ECLAC SantiagoCL, 2004)
Analyzes the socio-economic effects of Hurricane Mitch using a gender aproach. Proposes new analysis indicators for crisis situations that may better reflect women's disadvantageous position relative to men.